Developing and selecting interventions for translating knowledge to action - Wensing, Michel; Bosch, Marije Caroline; Grol, Richard (Cmaj, 2010)
Once knowledge has been adapted to local context and the barriers to and facilitators of use of knowledge have been identified, [1][1] we must select, tailor and implement interventions for the uptake of knowledge. [2][2] This article provides an approach to selecting interventions for knowledge